Mesin Miling CNC Router 3-Axis Untuk Pembuatan Canting Batik Cap Berkualitas Biaya Murah - Sarana (Jurusan Akuntansi, Politeknik Negeri Semarang), Suharto, Suryanto (Jurusan Teknik Mesin, Pol (Teknis, 2016)
Making of batik stamp conventionally can only be done by experts in order to form a opper ribbon to be batik image as planned according to the designed batik. Time to createeach batik stamp could be four weeks, so the price is expensive. Constraints of time and theexpensive prices for the process of making batik stamp are likely to be overcome by the application of milling machine 3 axis CNC router. The aim of this study was to analyze the design of batik stamp made of aluminum plate using CNC milling machines Router 3 Axis viewed from the aspect of technology, economics, and human resources.The method applied is enginering design approach that includes (1) identification of design considerations: batik images that are complex and unique, material of the stamp, long processing time,Â  expensive price, and the process of batik tasting; (2) The application of CNC milling machine router 3 axis: design of batik stamp made from aluminum plate,engineering applications software coreldraw, aspire vectric, mach-3, and the manufacture of batik stamp with CNC milling machines, analyzes the results of batik stamp regaring technological aspects, economic, and human resources. The results of this study indicate that the batik stamp made from aluminum plate using CNC milling machines have the technological and economic feasibilities. Transition of making stamped batik conventionally to applications of router axis CNC milling machines for batik communities still constrained by social and cultural issues.Keywords: CNC milling machine, batik stamp, engineering software